"The Grand Bargain": Detroit's financial fall to bankruptcy and rise to new possibilities - John Naglick; Martin Lavelle; John A. Moore (Essays in Economic & Business History (EEBH), 2020)
The City of Detroit filed a petition for bankruptcy on July 18, 2013. At the time, it represented the largest municipal bankruptcy in American history. On November 12, 2014 a complex settlement agreement was accepted by the United States Bankruptcy Court. Causes leading to Detroit's bankruptcy traced back several decades. Yet, Detroit's emergence from bankruptcy only took about five hundred days. The problems leading to the City's financial crisis are not unique to Detroit. Technological change, demographic shifts, faulty financial decisions and other variables that plagued Detroit are present in other American public entities. It is inevitable that there will be larger public bankruptcies in the future. The value of Detroit's story, however, is the example of how its financial crisis was resolved through the creative resolution process that involved the Court, the City and the wide circle of its financial stakeholders. Detroit's bankruptcy creates a valuable historical benchmark and its lessons can greatly impact how future public bankruptcies in the United States are resolved.
Keywords: 330